1966
DOI: 10.1159/000279422
|View full text |Cite
|
Sign up to set email alerts
|

Immunreaktionen bei Fertilitätsstörungen des Mannes

Abstract: Die bisherigen experimentellen und klinischen Untersuchungen über immunbiologische Probleme bei Fertilitätsstörungen des Mannes sind in ein Stadium getreten, in dem sie auch für die praktische Abklärung von Fertilitäts- und Sterilitätsfragen eine gewisse Bedeutung erlangt haben. In der vorliegenden Arbeit wurden die wichtigsten bisher bekannten Untersuchungsergebnisse auf diesem Gebiet angeführt. In eigenen Untersuchungen über die antigenen Eigenschaften von menschlichem Samenplasma, Spermatozoen und kochsalzl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

1968
1968
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…This agrees with reports by Bandhauer (1966) and Cruickshank & Stuart-Smith (1959) who found no anti-seminal precipitins in sera containing agglutinins from men with orchitis. Moreover, Isojima et al (1968) showed that precipitation was very much less sensitive than agglutination in detecting antispermatozoal antibodies in a rabbit antiserum.…”
Section: Preeipitation In Agar Gelssupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with reports by Bandhauer (1966) and Cruickshank & Stuart-Smith (1959) who found no anti-seminal precipitins in sera containing agglutinins from men with orchitis. Moreover, Isojima et al (1968) showed that precipitation was very much less sensitive than agglutination in detecting antispermatozoal antibodies in a rabbit antiserum.…”
Section: Preeipitation In Agar Gelssupporting
confidence: 93%
“…Several techniques have been used to detect anti-seminal or anti-spermatozoai antibodies in women and men, particularly precipitation in agar gels (Bandhauer, 1966). agglutination of spermatozoa (Kibrick et al, 1952;Rumke, 1959Rumke, , 1965, the tanned red cell agglutination test (Southam, 1963;Schwimmer et al, 1967a;Tsojima et aly 1968).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism may also playa part in the production of oligozoospermia sometimes seen with unilateral testicular obstruction, associated with normal spermatogenesis and positive antisperm antibodies (Hendry 1994), a syndrome that was first described over 20 years ago (Bandhauer 1966) but which still often escapes recognition in the subfertile male. However, this diagnosis should not be missed if antisperm antibodies are always measured prior to surgical exploration.…”
Section: Empty Epididymesmentioning
confidence: 99%
“…The first investigation, focusing on this problem, was performed by Bandhauer [2] who studied sera from 24 patients before, immediately after and 10 days after testicular biopsy. Sperm-agglutinating antibodies were not detected in any case but only titres of 32 or more were recorded.…”
Section: -6199/82/0138/0023/$0100mentioning
confidence: 99%